Sistem Informasi Berbasis Web Sebagai Media Promosi Pada Toko Sinar Baru Grande Prabumulih - Valentine, Lola; Suhartini, Suhartini; Setiawan, Iwan (Training & Research Institute - Jeramba Ilmu Sukses, 2024)
Web-based information systems, such as promotional media, provide information services through promotions. The researcher's goal is to provide convenience in promoting goods. The purpose of the study resulted in several uses consisting of practical and academic uses. The method used in this study uses a quantitative approach method that is descriptive to describe and illustrate a variable, symptom, condition, or certain social phenomenon, and its development method is Waterfall; the analysis tools used are Use case diagrams, Class diagrams, and Activity diagrams. This information system is built to provide convenience for consumers in viewing the latest products to make it easier and faster